The Effect of Gender Diversity, Experience, and Busyness of Directors on Integrated Reporting Disclosure (Study on Companies in India, Japan, and Malaysia) - Husna, Tsabita Pharama; Rosdini, Dini; Fatmawati, Faoziah Ulfah (Journal of Accounting Auditing and Business, 2024)
This study aims to determine the effect of gender diversity, experience diversity, and busyness diversity on integrated reporting disclosure. This study uses data on directors and integrated reporting of top 30 companies from Asian countries, namely India, Japan, and Malaysia, resulting in 101 samples during the observation time of 2020-2022. The sample determination used a purposive sample method. The independent variable is measured using the Blau Index while the dependent variable is measured using the Integrated Reporting Checklist. The data obtained was then analyzed using descriptive analysis and multiple linear regression.The results of this study indicate that gender diversity and experience diversity influence integrated reporting disclosure. Meanwhile, the board of directors' busyness diversity has no effect on integrated reporting disclosure. Simultaneously gender diversity, experience diversity, and the diversity of directors' busyness together affect the disclosure of integrated reporting.